The Use of Caricature Media in Indonesian Language Learning to Improve Writing Skills - Sulistiani, Sulistiani (Yayasan Darusssalam Bengkulu, 2020)
The purpose of this study is to describe that the use of caricature media in Indonesian language learning can improve argumentation writing skills in class X.1 SMA Negeri 1 Mejayan. This study uses a Classroom Action Research approach, which is a study which is a form of collaboration / collaboration between researchers, teachers and students. The data sources of this research are: informants (Indonesian language teachers, students, vice principal in the curriculum field), places and events (learning activities to write arguments in class X.1 SMA Negeri 1 Mejayan), documents (caricature pictures). The data collection techniques used were interview, observation, test, and questionnaire techniques. The data collection technique used the method triangulation technique, data source triangulation, and informant review to determine the validity of the data. The data analysis technique used is to do a qualitative description that is adjusted to the predetermined success indicators. The research process was carried out in three cycles, each cycle consisting of four stages: (1) preparation, (2) implementation, (3) monitoring and evaluation, (4) analysis and reflection. Based on the research results, it can be concluded that caricature media can improve the Indonesian language learning process as well as the argumentation writing skills of class X SMA Negeri 1 Mejayan. This is reflected in several indicators of success as follows: (1) students 'interest in taking writing lessons increases, (2) teachers are able to arouse students' interest, (3) students are able to determine topics and arguments to be made in argumentative writing, (4) the teacher able to use caricature media in learning to write arguments, (5) the teacher is able to manage the class well, (5) the students' argumentation writing skills continue to improve from cycles I, II, and III.